Peanuts : A Charlie Brown Christmas - Schulz, Charles M.; Korman, Justine; Fontes, Ron; Mendelson, Lee.; Melendez, Bill.; Braddock, Paige (New York, NY : Little Simon, 2002)
Surrounded by other kids with extremely commercial ideas about Christmas, Charlie Brown struggles to understand the true spirit of the holiday.
On disc: Christmas is coming (Guaraldi) (3:22) -- Skating (Guaraldi) (2:24) -- Linus and Lucy (Guaraldi) (3:03) -- Christmas time is here [instrumental] (Guaraldi-Mendelson) (6:06).
"Based on the television special produced by Lee Mendelson and Bill Melendez."
"Adapted from the works of Charles M. Schulz."
Includes music compact disc "From the album 'A Charlie Brown Christmas' (Fantasy 8431)."
Keywords: Christmas stories; Peanuts (Comic strip) -- Fiction; Brown, Charlie (Fictitious character) -- Fiction; Christmas -- Fiction; Picture book